2015
DOI: 10.1016/j.myc.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation and experimental host range of Alternaria cinerariae

Abstract: a b s t r a c tAlternaria cinerariae, an important and well-known plant pathogen of cineraria, has been delimited by its narrowly to broadly ellipsoid or ovoid conidia with blunt-tapered false beaks, but without descriptions of its morphological variability and host range. Leaf spot diseases have recently been found on asteraceous plants Pericallis cruenta, Farfugium japonicum, and Gynura bicolor in Japan, with A. cinerariae-like isolates subsequently obtained from the lesions. In this study, we identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Notes: Morphological variations are present between strains, including the appearance of excessively swollen bodies and chlamydospore (microsclerotia) formation (Nishikawa & Nakashima 2015). There is no ex-type culture and few reference isolates, and the epitype originated near the original type locality; therefore, an ex-epitype isolate was designated and deposited for future studies.…”
Section: Japanese Species Of Alternariamentioning
confidence: 99%
See 1 more Smart Citation
“…Notes: Morphological variations are present between strains, including the appearance of excessively swollen bodies and chlamydospore (microsclerotia) formation (Nishikawa & Nakashima 2015). There is no ex-type culture and few reference isolates, and the epitype originated near the original type locality; therefore, an ex-epitype isolate was designated and deposited for future studies.…”
Section: Japanese Species Of Alternariamentioning
confidence: 99%
“…However, their morphological variation and fundamental pleomorphism complicated species recognition, and thus host plants played a key role in identification. Due to their ubiquitous nature, this approach led to a false inflation of species numbers, resulting in the genus containing more than 400 species (Nishikawa & Nakashima 2015, Lawrence et al 2016. The introduction of a molecular phylogenetic approach has again helped to clarify their taxonomy, reducing many allied genera into one large genus, Alternaria (Woudenberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the pathogenicity tests revealed that the fungus is the causal agent causing leaf spot and blight disease on the host. Nishikawa and Nakashima [ 19 ] had been tested the pathogenicity of A. cinerariae on C. coronarium ( Glebionis coronaria ) and found it to be non-pathogenic on this plant.…”
Section: Pathogenicity Testsmentioning
confidence: 99%
“…The colony characteristics were consistent with those known for Alternaria alternata (Simmons 2007). The ITS, gpd, Alt-a1, and tef1 gene regions were amplified using primer pairs ITS1/ITS4, gpd1/gpd 2, Alt-for/Alt-rev, and EF1-728F/ EF1-986R, respectively (Nishikawa and Nakashima 2015;Woudenberg et al 2014). The sequences were deposited in GenBank: MN636331 (ITS), MT012958 (gpd), MT140362 (Alt-a1), and MT133312 (tef1).…”
mentioning
confidence: 99%